2009
DOI: 10.1179/026708408x370221
|View full text |Cite
|
Sign up to set email alerts
|

Influence of electrosynthesis potential on corrosion performance of polypyrrole coated stainless steel and its mechanism research

Abstract: The electrosynthesis process of conducting polymer on stainless steel was investigated and a two-step process was adopted to obtain polypyrrole (PPy) films at low potentials. The effects of applied potentials on the electrochemical, structural and protective properties of PPy films have been explored using scanning electron microscopy, infrared spectroscopy, cyclic voltammetry, open circuit potential and potentiodynamic polarisation. Films electrodeposited at lower potentials have more homogeneous morphology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Using this initial potential, the optimum upper potential limit was examined by electrodepositing PNMPy at various upper potential limits (+0.9 and +1.0 V) while keeping the scan rate (20 mV/s) and cycle numbers (20 cycles) fixed. Meanwhile, it was reported that polymer films will be irreversibly overoxidized at high potentials resulting in loss of conductivity and electroactivity as well as degradation of mechanical properties. , The overoxidation of polymer film also leads to an increase in its permeability, thus the coating becomes less protective and the applied potential is also expected to affect the corrosion performance of the polymer film. In order to prevent further oxidation of the polymer film, Tüken et al limited the upper potential at +0.85 V during the cyclic voltammetric synthesis of PNMPy on a mild steel electrode in 0.3 M oxalic acid medium .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using this initial potential, the optimum upper potential limit was examined by electrodepositing PNMPy at various upper potential limits (+0.9 and +1.0 V) while keeping the scan rate (20 mV/s) and cycle numbers (20 cycles) fixed. Meanwhile, it was reported that polymer films will be irreversibly overoxidized at high potentials resulting in loss of conductivity and electroactivity as well as degradation of mechanical properties. , The overoxidation of polymer film also leads to an increase in its permeability, thus the coating becomes less protective and the applied potential is also expected to affect the corrosion performance of the polymer film. In order to prevent further oxidation of the polymer film, Tüken et al limited the upper potential at +0.85 V during the cyclic voltammetric synthesis of PNMPy on a mild steel electrode in 0.3 M oxalic acid medium .…”
Section: Resultsmentioning
confidence: 99%
“…As immersion goes on, PNMPy film will loose its electroactivity, thus the ability to reduce and oxidize successively and reversibly, vanishes. The successive and reversible conversion of doped form to undoped form may induce fatigue-like stress that could be responsible for cracking …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electrically conducting polymers such as polypyrrole (PPy) are particularly promising owing to their highly electrical conductivity, corrosion performance, ease of low cost synthesis and environmental stability. 13,14 However, the disadvantages of PPy can not be ignored, such as not easily soluble in common organic solvents, processing difficulties and relatively low conductivity, which has limited the application of PPy in practice. 15 In order to improve the properties of PPy, a series of conducting PPy composites were prepared by using graphite/graphene as the conducting filler to explore their potential applications as high-performance materials.…”
Section: Introductionmentioning
confidence: 99%